The impact of the microbiota-gut-brain axis on endometriosis-associated symptoms: mechanisms and opportunities for personalised management strategies - Francesca Hearn-Yeates; Andrew W Horne; Siobhain M O'Mahony; Philippa T K Saunders (Bioscientifica, 2024)
Endometriosis is a chronic inflammatory condition affecting one in ten women and those assigned female at birth, defined by the presence of endometrial-like tissue outside the uterus. It is commonly associated with pain, infertility, and mood disorders, and is often comorbid with other chronic pain conditions, such as irritable bowel syndrome. Recent research has identified a key role for the microbiota-gut-brain axis in health and a range of inflammatory and neurological disorders, prompting an exploration of its potential mechanistic role in endometriosis. Increased awareness of the impact of the gut microbiota within the patient community, combined with the often-detrimental side effects of current therapies, has motivated many to utilise self-management strategies, such as dietary modification and supplements, despite a lack of robust clinical evidence. Current research has characterised the gut microbiota in endometriosis patients and animal models. However, small cohorts and differing methodology have resulted in little consensus on the data. In this narrative review, we summarise research studies that have investigated the role of gut microbiota and their metabolic products in the development and progression of endometriosis lesions, before summarising insights from research into co-morbid conditions and discussing the reported impact of self-management strategies on symptoms of endometriosis. Finally, we suggest ways in which this promising field of research could be expanded to explore the role of specific bacteria, improve access to 'microbial' phenotyping, and develop personalised patient advice for reduction of symptoms such as chronic pain and bloating.